2020
DOI: 10.1080/19475705.2020.1734102
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on mining-induced strain and failure characteristics of rock masses of mine floor

Abstract: (2020) Experimental investigation on mining-induced strain and failure characteristics of rock masses of mine floor,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 42 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…In addition, compared with the PCA method, PLS-DA has the function of quantifying the degree of difference between different water sources caused by the characteristic water chemical composition. The loading scatter plots of PCA and PLS-DA both showed that TDS, HCO t [3] t [1] t [2] t [3] Figure 8: Schematic diagram of the PLS-DA model in threedimensional space. 100: fourth aquifer water; 010: coal-bearing sandstone aquifer water; 001: limestone aquifer water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, compared with the PCA method, PLS-DA has the function of quantifying the degree of difference between different water sources caused by the characteristic water chemical composition. The loading scatter plots of PCA and PLS-DA both showed that TDS, HCO t [3] t [1] t [2] t [3] Figure 8: Schematic diagram of the PLS-DA model in threedimensional space. 100: fourth aquifer water; 010: coal-bearing sandstone aquifer water; 001: limestone aquifer water.…”
Section: Discussionmentioning
confidence: 99%
“…Coal resource is an important basic resource for the longterm rapid and stable development of the national economy in China [1]. As mining depth has increased, water inrush disaster occurrence has also increased, which poses a serious threat to the safety of coal mine production [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The mined-out areas formed during the mining of metal mines lead to the movement and fragmentation of rock layers, which in turn causes surface settlement in the mining area, unbalanced ecological environment, and even a series of problems such as safety accidents (Yang et al, 2017;Xu et al, 2019a;Huang et al, 2019;Zeng et al, 2020;Zheng et al, 2021). Meanwhile, a large number of tailings will inevitably be produced in the process of mineral processing.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior changes the stability of regional geological structure and then affects the mining efficiency and safety of underlying coal seam. At present, many scholars have studied the changes of mineral composition and chemical characteristics of overlying rock and soil after being baked by coal fire (Khoury 2020b;Zhang et al 2020;Savina et al 2020;Sokol et al 2020;Chen et al 2020); however, the physical and mechanical properties and pore structure characteristics of pyrometamorphic rocks caused by coal fire have not been widely concerned (Zeng et al 2020).…”
Section: Introductionmentioning
confidence: 99%